การบริหารแบบสมดุลกับคุณลักษณะโรงเรียนมาตรฐานสากล สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา - ซาไข ปัณณวิชญ์; รัตนศิระประภา นุชนรา (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์ เพื่อทราบ 1) การบริหารแบบสมดุลของโรงเรียนมาตรฐานสากล สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา 2) คุณลักษณะโรงเรียนมาตรฐานสากล สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา 3)ความสัมพันธ์ระหว่างการบริหารแบบสมดุลกับคุณลักษณะโรงเรียนมาตรฐานสากล สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาเครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถามความคิดเห็นที่ผู้วิจัยได้พัฒนาขึ้นเอง ตัวอย่างที่ใช้ในการวิเคราะห์ครั้งนี้ คือ โรงเรียนมัธยมศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา จำนวน 34 โรงเรียน ผู้ให้ข้อมูลโรงเรียนละ 4 คน ประกอบด้วย ผู้อำนวยการโรงเรียน รองผู้อำนวยการโรงเรียน และครู 2 คน รวมทั้งสิ้น 112 คน สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ การแจกแจงความถี่ และค่าร้อยละ ค่ามัชฌิมเลขคณิต และส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์ค่าสัมประสิทธิ์สหสัมพันธ์ของเพียร์สัน ผลการวิจัยพบว่า 1. การบริหารแบบสมดุลของโรงเรียนมาตรฐานสากล สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา ทั้งภาพรวมและรายด้านอยู่ในระดับมาก โดยเรียงจากมากไปหาน้อยได้ ดังนี้ 1) มุมมองด้านการเรียนรู้และการเติบโต 2) มุมมองด้านกระบวนการภายใน 3) มุมมองด้านการเงิน และ 4) มุมมองด้านลูกค้า 2. คุณลักษณะโรงเรียนมาตรฐานสากล สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา โดยภาพรวมอยู่ในระดับมาdโดยเรียงจากมากไปหาน้อยได้ ดังนี้ 1) การบริหารจัดการระบบคุณภาพ 2) การจัดการเรียนการสอนเทียบเคียงมาตรฐานสากล และ 3) ผู้เรียนมีศักยภาพเป็นพลโลก 3. การบริหารแบบสมดุลกับคุณลักษณะโรงเรียนมาตรฐานสากล สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา โดยภาพรวมและรายด้าน มีความสัมพันธ์กันอย่างมีนัยสำคัญทางสถิติ ที่ระดับ .01 THE BALANCE SCORECARD MANAGEMENT AND THE CHARACTERISTICS OF WORLD CLASS STANDARD SCHOOL UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE The purposes of this research were to determine 1) the balanced scorecard management of world class standard school under the secondary educational service area office, 2) the characteristics of world class standard school under the secondary educational service area office, 3) the relationship between balanced scorecard management and characteristics of world class standard school under the secondary educational service area office. The research instrument was a questionnaire. The sample were 34 world class standard school under the secondary educational service area office. The respondents were school director, assistance school director and 2 teachers total 112 respondents. The statistics used for analysis the data were frequency, percentage, arithmetic mean, standard deviation and Pearson’s Product Moment Correlation, Coefficient. The findings revealed as follows: 1. The balanced scorecard management of world class standard school under the secondary educational service area office as a whole and individual was at a high level; ranking from the highest to the lowest mean as follows: learning and growth perspective, internal process perspective, financial perspective and customer perspective. 2. The characteristics of world class standard school under the secondary educational service area office as a whole and as individual, were at a high level; ranking from the highest to the lowest mean as follows: the quality system management,the world class standard curriculum and instruction and the world citizen. 3. The balanced scorecard management and characteristics of world class standard school under the secondary educational service area office as a whole and an individual, was significantly correlated at 0.1 level of significant